Evaluation of immunotoxicity of the extended-release form of Afobazol - L. P. Kovalenko; R. V. Zhurikov; K. V. Korzhova; A. D. Durnev (LLC "Publisher OKI", 2021)
The research of immunotoxicity of extended-release form of Afobazol was conducted on male CBA, C57BL/6 and F1 hybrids (CBA×C57BL/6) mice. Afobazol was administered per os for 14 days in doses of 12 mg/kg and 120 mg/kg. Control group received a placebo. Weight of thymus, spleen and popliteal lymph nodes was not affected by the extended-release form of Afobazol in doses of 12 mg/kg and 120 mg/kg in F1 hybrids (CBA×C57BL/6) mice compared to the control group (p> 0.05). Cellularity of thymus was significantly increased by the extended-release form of Afobazol in dose of 12 mg/kg (p< 0.01 vs control group). Administration of the extended-release form of Afobazol in doses of 12 mg/kg and 120 mg/kg decreased spontaneous chemiluminescence activity of peripheral blood lymphocytes in 2.0 and 2.2 times, in dose of 120 mg/kg level integral chemiluminescence response S was decreased in 2.4 times (p< 0.05 vs control group). Phagocytic activity of peritoneal macrophages and antibody production in F1 hybrids (CBA×C57BL/6) mice were not affected by administration of the extended-release form of Afobazol in doses of 12 mg/kg and 120 mg/kg (p > 0.05 vs control group). 14 days of the extended-release form of Afobazol in doses of 12 mg/kg and 120 mg/kg did not cause any significant change to intensity of delayed-type hypersensitivity reactions (p> 0.05 vs control group). The results of the study allow us to conclude that administration of the extended-release form Afobazol in the range of studied doses does not induce immunotoxicity.